2020
DOI: 10.1111/pcmr.12866
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell receptor diversity as a prognostic biomarker in melanoma patients

Abstract: There is increasing evidence that T‐cell receptor (TCR) repertoire diversity can be a predictive biomarker of immune responses in cancer patients. However, the characteristics of the T‐cell repertoire together with its prognostic significance in melanoma patients and impact on disease progression remain unknown. We investigated the combinatorial TCR repertoire diversity by semi‐quantitative multi‐N‐plex PCR in peripheral blood samples from 44 melanoma patients together with seven matched metastatic lymph nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
(32 reference statements)
2
12
0
1
Order By: Relevance
“…A recent report by Shahamatdar et al 46 analyzing germline variants in the TCGA cohort demonstrated that host genetics are associated with phenotypes that describe the immune component of the tumor microenvironment; they found one SNP associated with the amount of infiltrating follicular helper T cells; and 23 candidate genes, some of which are involved in cytokine-mediated signaling. Our patient cohort supports prior findings that patients with greater TCR richness in the peripheral blood had improved survival compared with patients with less clonal richness 47-49 . TCR richness declined with chemoradiation although a smaller mid-treatment decline in TCR diversity was associated with improved survival.…”
Section: Discussionsupporting
confidence: 88%
“…A recent report by Shahamatdar et al 46 analyzing germline variants in the TCGA cohort demonstrated that host genetics are associated with phenotypes that describe the immune component of the tumor microenvironment; they found one SNP associated with the amount of infiltrating follicular helper T cells; and 23 candidate genes, some of which are involved in cytokine-mediated signaling. Our patient cohort supports prior findings that patients with greater TCR richness in the peripheral blood had improved survival compared with patients with less clonal richness 47-49 . TCR richness declined with chemoradiation although a smaller mid-treatment decline in TCR diversity was associated with improved survival.…”
Section: Discussionsupporting
confidence: 88%
“…A recent report by Shahamatdar et al 46 analyzing germline variants in the TCGA cohort demonstrated that host genetics are associated with phenotypes that describe the immune component of the tumor microenvironment; they found one SNP associated with the amount of infiltrating follicular helper T cells; and 23 candidate genes, some of which are involved in cytokinemediated signaling. Our patient cohort supports prior findings that patients with greater TCR richness in the peripheral blood had improved survival compared with patients with less clonal richness [47][48][49] . TCR richness declined with chemoradiation although a smaller mid-treatment decline in TCR diversity was associated with improved survival.…”
Section: Discussionsupporting
confidence: 88%
“…Our patient cohort supports prior findings that patients with greater TCR richness in the peripheral blood had improved survival compared with patients with less clonal richness. 46 , 47 , 48 TCR richness declined with chemoradiation although a smaller midtreatment decline in TCR diversity was associated with improved survival. Pretreatment TCR clone distribution slope, among other diversity metrics, was correlated with PET response status, but none of the TCR diversity metrics were correlated with midtreatment residual TLG.…”
Section: Discussionmentioning
confidence: 94%
“…Probably, homeostatic proliferation can also contribute to a decrease in the general diversity of TCRs and the TCR diversity of naïve T cells with age (23), which negatively affects the protective function of the immune system against infections or other antigenic challenges in senior age (23,164). It was shown that increased sensitivity to viral and oncological disease was associated with a decrease in the diversity of TCRs and connected with the formation of holes in the TCR repertoires (164)(165)(166)(167).…”
Section: Potential Risks Of Immune Disequilibriummentioning
confidence: 99%